Peran Pemerintah dan Strategi Penguatan Ekonomi Kerakyatan dalam Pemberdayaan UMKM Go Digital di Purwokerto - Pratama, Bagus Hendra Stia; Maghfiroh, Siti; Sifa, Abdan; Rohmah, Kuni Naela; Ridwan, Muhammad; Sofiah, Ulfatus (FEB Universitas Maritim Semarang, 2024)
This article discusses the role of the government and strategies for strengthening the people's economy in empowering Micro, Small, and Medium Enterprises (MSMEs) in Purwokerto, particularly in the context of digitalization. MSMEs play a significant role in the local and national economy but face various challenges that affect their competitiveness. The Banyumas Regency government actively supports digital transformation through training and programs that enhance the digital skills of MSME actors. Additionally, financial literacy is also deemed crucial to help MSME actors manage finances and understand essential business aspects. This article aims to provide an in-depth understanding of the conditions of MSMEs in Purwokerto and the steps that can be taken to enhance their role in the local economy.